Cover Crops Impacts on Louisiana Corn Production and Soil Properties. Issue 1 (1st July 2019) - Sanchez, Ina; Fultz, Lisa M.; Lofton, Josh; Haggard, Beatrix
Abstract : Core Ideas: Combination of cover crops with conservation tillage increased soil C. Cover crops significantly reduced nitrate‐N levels during the fallow season. Legume cover crops reduced N requirements when compared with non‐legumes. Conventionally managed, continuous monoculture row‐crop production has depleted the soil of nutrients, organic matter, and overall productivity. This has increased the need for external inputs, specifically N, to meet crop demand. Despite the growing interest in conservation practices, including minimal tillage and cover crops, little work has been reported in the Mid‐South region. Cereal rye ( Secale cereal L.), forage radish ( Raphanus sativus var. longipinnatus L.), berseem clover ( Trifolium alexandrinum L.), crimson clover ( Trifolium incarnatum L), winter pea ( Pisium sativum L), hairy vetch ( Vicia villosa Roth), and a cereal rye–forage radish mix were seeded in discrete blocks in October 2014, 2015, and 2016 along with a non‐cover fallow. Each block was divided into 16 sub‐plots to which one of four N fertilizer rates (0, 235, 268, and 302 kg N ha −1 ) were applied. Corn ( Zea mays L.) grain yields increased with additions of N fertilizer; however, no difference was observed between the three fertilizer rates in 2 of 3 yr. Cover crops aided in the uptake and recycling of inorganic N, potentially reducing losses and providing N for subsequent cash crops. Following legume cover crops, corn grain yields were maximized with the addition of 235 kg N ha −1 . Inclusion of grass and brassicas with no additional N input reduced corn grain yield, which remained lower than yield measured following legumes up to the 302 kg N ha −1 rate. Secondary benefits of cover crops included increased soil C (36%) and N (22%), and N cycling over a 2‐yr period.